Examining factors that influence alumni giving from traditional and online MBA alumni at Colorado State University - Guild, Erin, author; Kuk, Linda, advisor; Kaiser, Leann, committee member; Kaminski, Karen, committee member; Weiss, John, committee member (Colorado State University. Libraries, 2018)
Increasingly, institutions of higher education seek out alumni support to help offset budget cuts and look toward technological advances to lower costs of instruction and create new revenue streams. In light of the desire to increase funding for university programs and the potential giving-power of MBA alumni, this study investigates factors that influence alumni giving from traditional and online MBA alumni. The relationship between sense of community, alumni demographics and donor behavior and attitudes is explored to consider factors that might predict alumni giving behavior and attitudes. This quantitative study uses logistic regression and independent samples test statistical methods to reveal that the odds of an alumnus making a financial donation are increasingly greater as age increases and as gender is female. Analysis also suggests that the odds of an alumnus making a financial donation are increasingly greater as sense of community increases. Statistical analysis shows that online CSU MBA alumni are different than traditional face-to-face CSU MBA alumni on sense of community, whereby the sense of community score for the online alumni is significantly lower than the score for traditional face-to-face alumni. Analysis in this study also demonstrates, however, that online alumni do not differ from face-to-face alumni on the following characteristics: age; donor status; attitude toward giving; gender; citizenship; and race/ethnicity.